Métrica para definição de pontos estáveis utilizando-se da Análise de Robustez no posicionamento por ponto preciso - Cavalheri, Emerson Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Deformation monitoring of large structures or land surface, the displacement of the investigated points are usually obtained according to points located outside of the studied body and they are considered to be stable (reference points) in the analysis. If these constrained points, assumed as references, in reality are not stable the nal parameters will be directly in uenced by this consideration. To establish a reference network stable points must be found, i.e, those that least move over time. The instability or displacements in the point position with respect to time can be separated into two types: continental and local. The continental displacements treat the su ered motion by the station on the basis of the continental speed, that is, due to the plate movement that the point is locate. The local displacements are obtained as function of physical phenomena of the local geology, they may or may not have a pattern of variation. Local movements are the only of extreme interest in the de nition of stable points. Thus, this work proposes a strategy for classi cation of stable points by using these obtained displacements without the in uence of continental displacements in the station position. Based on coordinate time series obtained from the PPP (Precise Point Positioning) processing method with the GAPS (GPS Analysis and Positioning Software) software, comparing them to coordinates obtained from a velocity model, e.g., the VEMOS2009 (Velocity Model for South America and the Caribbean), is intended to de ne a metric for classi cation of stable points, where the Network Robustness Analysis is adopted as a statistical criterion for evaluation of the proposed mathematical model...

No monitoramento de deformações de grandes estruturas ou da superfície terrestre, o deslocamento dos pontos investigados geralmente são obtidos em função de pontos localizados fora do corpo de estudo e são considerados como estáveis (pontos de refer ência) nas análises. Se estes pontos, assumidos como referências, na realidade não forem estáveis, os parâmetros nais serão in uenciados diretamente por esta considera ção. Para estabelecer uma rede de referência pontos estáveis devem ser encontrados, ou seja, aqueles que menos se movimentam ao passar do tempo. A instabilidade, ou deslocamento, na posição de um ponto com relação ao tempo pode ser separados em dois tipos: continentais e locais. Os deslocamentos continentais tratam do movimento sofrido pela estação em função da sua velocidade continental, ou seja, devido ao movimento da placa em que se encontra. Já, os deslocamentos locais são obtidos em função de fenômenos físicos da geologia local, podendo ou não ter um padrão de variação. Os deslocamentos locais são os únicos de extremo interesse na de nição de pontos estáveis. Assim, este trabalho propõe uma estratégia para classi cação de pontos estáveis atrav és da obtenção destes deslocamentos sem a in uência dos deslocamentos continentais na posição da estação...
Keywords: Cartografia; Controle robusto; GPS (Programa de computador); Cartography